Dampak pelatihan dan pengembangan di industri retail - Alfin Ridho (CV Edujavare Publishing, 2023)
The text discusses the impact of training and development on employee performance in the retail industry. It highlights that the retail sector is growing rapidly and that the majority of the workforce in retail units are sales staff. The text suggests that continuous training and development programs have resulted in an increase in sales opportunities and that the effectiveness of employees has significantly increased, as per Stockdale and Kühne (2007). The text also states that the direct contact of employees with customers has a positive impact on the company's brand image. The text concludes that organizational efficiency, as determined by employee efficiency, is crucial for business success, as per Regis (2008). The text suggests that the income earned by the business unit depends on the efficiency of its employees, and that the program training and development can make the organization capable of achieving its goals, as per Haines and Bandth (2002). The text mentions that the income earned by the business unit determines the effectiveness of its employees, and that the program training and development can make the organization capable of achieving its goals. The text concludes that the concept of training and development is central to achieving organizational goals and a competitive advantage, and that the concepts of training and development include the program program training and development,the training system, the development of human resources, and the creation of organizational resources.